Effects of storage time and boiling on root tuber colour in two sweet potato [Ipomoea batatas L. (Lam.)] cultivars - Marti, Hector Ruben (Instituto Nacional de Investigación y Tecnología Agraria y Alimentaria, España, 2020)
The aim of this work was to determine the effect of storage time and boiling on the colour of sweet potato (cvs. Morada INTA and Regal) root tubers. Increasing storage time more strongly reduced the skin chroma (C*) of raw Morada INTA tubers than that of raw Regal root tubers. The skin hue angle (Hº) of raw Morada INTA tubers increased linearly with storage time; at the end of the experiment values were almost twice those at baseline. The results of this study suggest that the perception of skin-Hº is influenced by C*. In both cultivars, storage time more strongly affected the colour variables of the boiled than the raw flesh. Boiling led to a reduction in flesh luminosity (L*) and an increase in flesh-Hº. The interaction between cultivar and storage time appears to regulate the C* and Hº values of orange-flesh cultivars.